The African Charter on Human and Peoples' rights : a Charter of the african man ? : Contextual study based on the cultural features of african laws - (:unkn) unknown (My University, 2021)
The African Charter on Human and Peoples' Rights is the main regional text on the protection of human and peoples' rights. Before its adoption, many thought of adopting a continental text that would provide adequate protection for citizens' rights, especially in a period when certain countries were still under the yoke of colonial domination. The drafters of the Charter thus wanted to adopt a unique text of its kind that, that beyond providing the rights of individuals, also proclaims in its lines the rights of african peoples, including the fundamental right of peoples to self-government, a right that colonization has taken away from them. Nevertheless, can we really say that the African Charter is a text which reflects african legal cultures ? The history of Africa shows us that the continent, contrary to the prejudices of several europeancentrist authors, abounds in a very rich legal culture. Indeed, the existence of political and legal forms of organization on the continent is far from being a utopia. These traditions influence african social realities to this day. But the attachment invoked to universal human rights principles suggests that African cultures have somehow been scorned to make way for the universalism of modern human rights theories. This work therefore seeks to conduct a study of the legal context of african societies, to assess the degree to which african legal cultures are taken into account in the drafting of the Charter.
Keywords: African Research